Development of Certified Reference Materials for Diarrhetic Shellfish Poisoning Toxins, Part 1: Calibration Solutions. (4th December 2019) - Beach, Daniel G; Crain, Sheila; Lewis, Nancy; LeBlanc, Patricia; Hardstaff, William R; Perez, Ruth A; Giddings, Sabrina D; Martinez-Farina, Camilo F; Stefanova, Roumiana; Burton, Ian W; Kilcoyne, Jane; Melanson, Jeremy E; et al.
Abstract: Okadaic acid (OA) and its analogs dinophysistoxins-1 (DTX1) and -2 (DTX2) are lipophilic polyethers produced by marine dinoflagellates. These toxins accumulate in shellfish and cause diarrhetic shellfish poisoning (DSP) in humans. Regulatory testing of shellfish is essential to safeguard public health and for international trade. Certified reference materials (CRMs) play a key role in analytical monitoring programs. This paper presents an overview of the interdisciplinary work that went into the planning, production, and certification of calibration-solution CRMs for OA, DTX1, and DTX2. OA and DTX1 were isolated from large-scale algal cultures and DTX2 from naturally contaminated mussels. Toxins were isolated by a combination of extraction and chromatographic steps with processes adapted to suit the source and concentration of each toxin. New 19-epi-DSP toxin analogs were identified as minor impurities. Once OA, DTX1, and DTX2 were established to be of suitable purity, solutions were prepared and dispensed into flame-sealed glass ampoules. Certification measurements were carried out using quantitative NMR spectroscopy and LC-tandem MS. Traceability of measurements was established through certified external standards of established purity. Uncertainties were assigned following standards and guidelines from the International Organization for Standardization, with components from the measurement, stability, and homogeneity studies being propagated into final combined uncertainties.